‘Thare is na leid on life of lordship hym like’: linguistic means of depicting king arthur in the poem Golagros and Gawain - A. G. Stoliarova (Вестник Самарского университета: История, педагогика, филология, 2020)
It has recently been marked that the figure of king Arthur in Scottish literature is rather controversial: on the one hand, Arthur is a noble and valiant knight; on the other hand, he is an arrogant invader whose aim is to conquer the whole world. The contradictory nature of the figure of the legendary king results from the differences between English and Scottish political mythology: in Scotland by the late Middle Ages there had been developed its own legendary history, and the historical myth about Arthur as a king of the whole Britain had been interpreted as a threat to the national sovereignty. The paper focuses on the analysis of linguistic means of depicting king Arthur in one of the two surviving Scottish Arthurian romances, Golagros and Gawain written in the XVth century by an anonymous author. Golagros and Gawain continues the tradition of Middle English alliterative revival in Scotland in a local variety of the English language; the diction and style of this tradition are characterized by the use of substantive epithets, formulas, attributive complexes with alliterating elements. The research has shown that in Golagros and Gawainking Arthur is depicted as an honorable and generous, almost ideal ruler who returns to Golagros the independence he had earlier been deprived of. Kings dignity and nobility are emphasized in the poem with the help of traditional linguistic means of alliterative poetry: the qualities expressed in attributes are repeated several times with variations in poetic formulas and fixed in substantive epithets.